2018
DOI: 10.1136/bjophthalmol-2018-312934
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurement of optic nerve sheath diameter: a non-invasive surrogate approach for dynamic, real-time evaluation of intracranial pressure

Abstract: The current study aimed to identify whether ultrasonographic measurements of optic nerve sheath diameter (ONSD) could dynamically and sensitively evaluate real-time intracranial pressure (ICP). ONSD measurements were performed approximately 5  min prior to and after a lumbar puncture (LP). A total of 84 patients (mean±SD age, 43.5±14.7 years; 41 (49%) men; 18 patients with elevated ICP) were included in the study. The Spearman correlation coefficients between the two observers were 0.779 and 0.703 in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 33 publications
1
54
2
8
Order By: Relevance
“…Several adult studies have shown that POCUS of ONSD changes within minutes of pressure change, and demonstrated that the change in POCUS of ONSD is strongly correlated with changes in ICP (r = 0.67 to 0.90), implying that POCUS of ONSD could be used to dynamically detect real-time changes in ICP [ [31] , [32] , [33] , [34] , [35] ]. The median change in ONSD (ΔONSD) and change in ICP (ΔICP) were 0.11 mm and 30 mm H 2 O, respectively [ 32 ]. The other study investigated the effect of osmotic therapy on POCUS of ONSD in patients with increased ICP [ 36 ].…”
Section: Relevant Adult-specific Literaturementioning
confidence: 99%
“…Several adult studies have shown that POCUS of ONSD changes within minutes of pressure change, and demonstrated that the change in POCUS of ONSD is strongly correlated with changes in ICP (r = 0.67 to 0.90), implying that POCUS of ONSD could be used to dynamically detect real-time changes in ICP [ [31] , [32] , [33] , [34] , [35] ]. The median change in ONSD (ΔONSD) and change in ICP (ΔICP) were 0.11 mm and 30 mm H 2 O, respectively [ 32 ]. The other study investigated the effect of osmotic therapy on POCUS of ONSD in patients with increased ICP [ 36 ].…”
Section: Relevant Adult-specific Literaturementioning
confidence: 99%
“…6 Acute increases in ICP have been shown to strongly correlate with increases in ONSD. [7][8][9][10] Recently, ultrasound measurement of ONSD has been investigated for use as a dynamic real-time ICP monitoring tool in critically ill patients with promising results. 10 Ultrasound itself is becoming increasingly available due to decreasing costs, the production of portable pocket ultrasound systems, and the dissemination of ultrasound expertise.…”
Section: Introductionmentioning
confidence: 99%
“…However, those two studies used A‐scan ultrasonography 3,4 . As an increased number of studies, such as Reviews, Original researches, and Meta‐Analyses, have used B‐ultrasound as a noninvasive and useful method to analyze the relationship between ICP and ONSD, 5–9 we also choose the B‐ultrasound in our study, which was commonly used modality. Therefore, in the Introduction section, we have also cited a study mentioned that B‐scan which reported that ONSD would dilate in patients with increased ICP in 1989 10 .…”
mentioning
confidence: 99%